ANALYSIS OF STRATEGIES USED BY PT SEMEN INDONESIA TBK. IN ACHIEVING INTERNATIONAL MARKETING - Pratama, Alun; Fiqri Fauzi, Akhdintyaz; Anggriani Siregar, Putri Harum; Rizkaputra, Fergiawan Alfianto (Sekolah tinggi ilmu ekonomi pemuda, 2024)
This research discusses the role of international marketing strategy in the global expansion of PT Semen Indonesia Tbk using SWOT analysis. The research focuses on the utilization of the company's internal strengths, such as a positive reputation and integrated supply chain, in supporting expansion measures in international markets. The case study covers the acquisition of the Thang Long Cement plant in Vietnam, which expanded the company's market coverage in several countries including Vietnam, Singapore, and Bangladesh. Despite the success, political and legal risks in some countries posed challenges that needed to be addressed through risk diversification strategies and local partnerships. A deep understanding of cultural differences and consumer preferences in various markets was also identified as a key factor in achieving international marketing success for the company